EFEKTIVITAS FINANCIAL MANAGEMENT DAN OPERASIONAL MANAGEMENT PADA PENINGKATAN PRODUKTIVITAS KARYAWAN - A, Nuraningsih; Budiandriani, Budiandriani; Serang, Serlin (Universitas Muhammadiyah Tangerang, 2024)
In a company, employee productivity is very dependent on the company's ability to implement appropriate leadership in the company organization through both vertical and horizontal communication. In this research we used a research method, namely a qualitative approach. A qualitative approach is a research procedure that provides descriptive data or descriptions that can be built from observations. In short, a qualitative approach methodology is a methodology that utilizes qualitative data in the form of defining analysis or analysis through descriptive research. Financial management and operational management have an important role in business success at PT Bina Sarana Sulawesi, as in other places in the world. Some important financial management roles in Makassar are managing and allocating funds efficiently, maintaining financial health, developing long-term financial strategies, making wise investment decisions, and following applicable financial rules and regulations. However, the implementation of financial management in Makassar also faces several obstacles or obstacles, such as a lack of understanding and awareness about financial management, limited human resources, unique business environment challenges, and lack of access to financial resources. Therefore, there needs to be better awareness of the importance of financial management, development of quality human resources, and increased access to financial resources to implement effective financial management in Makassar.